On the soviet-period historiography of uzbekistan’s musical art and music education system - Murtazova, Sahodat Buriyevna (The Lingua Spectrum, 2026)
This article presents and analyzes selected scholarly works related to the historiography of Uzbekistan’s musical art and music education system during the Soviet period. Particular attention is paid to the dominance of the prevailing ideological framework, which significantly influenced historiographical studies and is clearly reflected in the works produced during that era. At the same time, the article highlights the emergence of substantial scholarly research devoted to the history of music and music education. It also provides information on the contributions of both Uzbek and Russian-speaking musicologists whose studies have played an important role in the development of the historiography of the field.